Prospects for ending the HIV epidemic among persons who inject drugs in Haiphong, Vietnam - Des Jarlais, Don C.; Thi Huong, Duong; Thi Hai Oanh, Khuat; Khuê Pham, Minh; Thi Giang, Hoang; Thi Tuyet Thanh, Nham; Arasteh, Kamyar; Feelemyer, Jonathan; Hammett, Theodore; Peries, Marianne; Michel, Laurent; Vu Hai, Vinh; et al. (The International journal of drug policy, 2016)
To examine the prospects for “ending the HIV epidemic” among persons who inject drugs (PWID) in Haiphong, Vietnam. Reaching an incidence of <0.5/100 person-years at risk (PY) was used as an operational definition for “ending the epidemic.” A respondent driven sampling study of 603 PWID was conducted from September to October 2014. Current heroin use (verified with urine testing and marks of injection) was an eligibility requirement. A structured questionnaire was administered by trained interviewers to obtain demographic, drug use, and risk behavior data; HIV counseling and testing and HCV testing was also conducted. Two methods (by assuming all new injectors were HIV negative at first injection and by slope of prevalence by years injecting) were used for estimating HIV among persons injecting for <5 years (“new injectors”). Comparisons were made to the HIV epidemic among PWID in New York City and modeling of the HIV epidemic in Can Tho province. HIV prevalence was 25% in 2014, down from 68% in 2006 and 48% in 2009; overall HCV prevalence in the study was 67%. Among HIV seropositive PWID, 33% reported receiving antiretroviral treatment. The great majority (83%) of subjects reported pharmacies as their primary source of needles and syringes and self-reported receptive and distributive syringe sharing were quite low (<6%). Estimating HIV incidence among non-MSM male new injectors with the assumption that all were HIV negative at first injection gave a rate of 1.2/100 person-years (95% CI −0.24, 3.4). Estimating HIV incidence by the slope of prevalence by years injecting gave a rate of 0.8/100 person-years at risk (95% CI −0.9, 2.5). The current HIV epidemic among PWID in Haiphong is in a declining phase, but estimated incidence among non-MSM new injectors is approximately 1/100 person-years and there is a substantial gap in provision of ART for HIV seropositives. Scaling up interventions, particularly HIV counseling and testing and antiretroviral treatment for all seropositive PWID, should accelerate the decline. Ending the epidemic is an attainable public health goal.